ANALISIS PENERAPAN PENJATUHAN SANKSI TINDAKAN KEBIRI KIMIA TERHADAP PELAKU KEJAHATAN SEKSUAL ANAK DITINJAU DARI SUDUT HAK ASASI MANUSIA PELAKU DAN KORBAN - Kevin Setiawan; Aji Wibowo (Jurnal Hukum Adigama, 2019)
Sexual crime is happening in various countries, especially in Indonesia. In general, sexual crimes, especially against children, are a concern by the government because when a child becomes a victim of sexual crimes it can cause life-long trauma and at worst, death. Therefore, the preventive ways has been arranged by the Governement in Law of Republic Indonesia Number 17 of 2016 concerning Determination of Substitute Government Regulations in Law of Republic Indonesia Number 1 of 2016 concerning the second amandement of Law number 23 of 2002 Regarding Child Protection where there are sanctions for chemical castration against perpetrators who commit sexual crimes against children, in order to provide a punishment that can make a deterrent effect on someone who commits sexual crimes against children. However, in the determination of sanctions for the act of chemical castration, the community and various parties have contradictions where it must be seen in terms of the human rights of the perpetrator and the effectiveness of the sanctions.